PENGARUH KOMUNIKASI MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL SWISS - BELINN SIMATUPANG JAKARTA - Maya Angraeni; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2019)
Purpose- This study aims to determine and analyze the influence of communication, motivation and work discipline on employee performance at the Hotel SwissBelinn Simatupang Jakarta. Design/methology/approach- The population in this study were employees who worked at Swiss-Beliin Simatupang Hotel Jakarta. The sampling technique uses saturated sample techniques and is obtained from 75 respondents. Data collection methods using questionnaires distributed to Swiss-Beliin Simatupang Jakarta hotel employees and analysis using Multiple Linear Regression. For the results of the validity and reliability test in this study has significant and real value. This research method uses quantitative descriptive. To test the classic assumptions in this study are tests of Normality, Heteroscedasticity, Multicollinearity, and Linearity to qualify for data. The collected data was then analyzed using SPSS version 20. Findings- It can be concluded that communication has a significant effect on employee performance by 92.4%, motivation has a significant influence on employee performance by 11.76%, the variable work discipline has a significant influence on performance employee. 10.82% and from this analysis it can be seen that Communication, Motivation, and Work Discipline have simultaneous effect on Employee Performance by 55.35% at Swiss-Beliin Simatupang Hotel Jakarta.